2012
DOI: 10.1063/1.3699039
|View full text |Cite
|
Sign up to set email alerts
|

Competing magnetic interactions and interfacial frozen-spins in Ni-NiO core-shell nano-rods

Abstract: Synthesis and magnetic characterization of Co-NiO-Ni core-shell nanotube arrays J. Appl. Phys. 110, 073912 (2011); 10.1063/1.3646491Ni-NiO core-shell nanoclusters with cubic shape by nanocluster beam deposition Appl. Phys. Lett. 90, 043111 (2007); This paper investigates the subtle interfacial magnetism of highly-aligned, free-standing Ni-NiO core-shell rods on a Si substrate, fabricated by electroless-plating and an anodic aluminum oxide template. Transmission electron microscopy found that the NiO shell was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Although EP struggles to produce intensely roughened and nanostructured metal films, these morphologies can be realized by postsynthetic treatments, such as thermal wrinkling of underlying polymer substrates . To obtain anisotropic nanostructures of special interest (e.g., metal nanotubes, nanowires (NWs), ,, nanorods, , or networks composed thereof), EP has to be combined with templates, which mold the deposit into such special shapes. To achieve the often desired target morphology of metal NWs, EP can be guided by either solid 1D templates (such as DNA assemblies or peptide fibers) or templates enclosing 1D pores (such as the nanochannels within track-etched polymers or mesoporous silica) .…”
Section: Introductionmentioning
confidence: 99%
“…Although EP struggles to produce intensely roughened and nanostructured metal films, these morphologies can be realized by postsynthetic treatments, such as thermal wrinkling of underlying polymer substrates . To obtain anisotropic nanostructures of special interest (e.g., metal nanotubes, nanowires (NWs), ,, nanorods, , or networks composed thereof), EP has to be combined with templates, which mold the deposit into such special shapes. To achieve the often desired target morphology of metal NWs, EP can be guided by either solid 1D templates (such as DNA assemblies or peptide fibers) or templates enclosing 1D pores (such as the nanochannels within track-etched polymers or mesoporous silica) .…”
Section: Introductionmentioning
confidence: 99%
“…The observed conventional exchange bias in Ni/NiO nanoparticles has been explained in a previous report by using a core/shell model with a higher concentration of nickel vacancies residing on the surface than in the core [ 7 , 8 ]. The field-cooling hysteresis loop has also been shown to shift vertically when measured below the freezing temperature ( T f ) [ 8 ], which can be assigned as due to the interfacial frozen spins originating from the strong pinning effect between Ni and NiO [ 13 ]. A similar interfacial frozen-spin-mediated exchange bias effect has also been observed from Fe/Fe 3 O 4 core/shell and Fe 3 O 4 hollow-shell nanoparticles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…More complex studies on the temperature-dependent magnetic properties of coreshell nanotubular structures, with a FM-AFM interfacial coupling, have also been reported (Hsu et al, 2012;Proenca et al, 2013a,d). In particular, the exchange-bias coupling between FM and AFM layers is expected to occur after field-cooling the AFM material from above its Néel temperature (Nogues and Schuller, 1999;Brems et al, 2005;Ventura et al, 2008;Maurer et al, 2009;Ali et al, 2012).…”
Section: Temperature-dependent Magnetic Propertiesmentioning
confidence: 85%
“…In particular, the exchange-bias coupling between FM and AFM layers is expected to occur after field-cooling the AFM material from above its Néel temperature (Nogues and Schuller, 1999;Brems et al, 2005;Ventura et al, 2008;Maurer et al, 2009;Ali et al, 2012). In fact, Hsu et al (2012) measured the exchange bias effect in core-shell Ni/NiO NRs at 50 K after field cooling the samples at AE30 kOe. Their work showed that the exchange bias effect in the studied nanostructures disappears at approximately 100 K, which was attributed to the vanishing of NiO pinning on Ni, yielding magnetic frustration at the core-shell interface.…”
Section: Temperature-dependent Magnetic Propertiesmentioning
confidence: 99%